养老服务社会化 ：中国养老服务业发展的必由之路 = Socialization of service for the elderly : inevitable tendency in the development of service industry for the elderly in China - 王保英 Wang, Baoying (2008)
In face of development of service industry for the elderly in China, there are two problems unchangable in reality: one is the sudden in crease of elderly population, the other is the weakening of the family caring ability for the elderly. In the circumstance of "Aged Before Rich" society of how to make full use of the social resource to improve the living quality of the elderly is a basic and inevitable question to develop the service for the elderly in China.